#ttc on Instagram: a multimodal discourse analysis of the treatment experience of patients pursuing in vitro fertilization - Bethany Johnson; Margaret M. Quinlan; Nathan Pope (Qualitative Research in Medicine & Healthcare)
While searching the Internet for health information is now commonplace, giving and receiving medical expertise on social media platforms such as Instagram (IG) is underexplored. In order to investigate the ways in which social media platforms are a resource for seeking medical expertise, we employed a multimodal discourse analysis; specifically, we focused on the hashtag #ttc and the engagement of the IG community it comprised. We examined three main themes around medical expertise during treatment indexed by the hashtag: treatment protocol choices, treatment side effects and pregnancy diagnosis/confirmation. Our findings suggest that social media platforms provide a new arena in which patients can challenge medical expertise by circumventing it or adopting lay expertise instead of practitioner suggestions. We close with research implications and suggestions for further research.